2009
DOI: 10.1016/j.jpainsymman.2007.08.019
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Fatigue in Chronic Illness: A Systematic Review of Unidimensional and Multidimensional Fatigue Measures

Abstract: Fatigue is a common symptom associated with a wide range of chronic diseases. A large number of instruments have been developed to measure fatigue. An assessment regarding the reliability, validity, and utility of fatigue measures is time-consuming for the clinician and researcher, and few reviews exist on which to draw such information. The aim of this article is to present a critical review of fatigue measures, the populations in which the scales have been used, and the extent to which the psychometric prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
278
1
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(290 citation statements)
references
References 111 publications
3
278
1
8
Order By: Relevance
“…As such, the results of this exploratory study should be cautiously interpreted. Although the MFI purports to assess five dimensions of fatigue, these dimensions have not been wholly replicated [49]. Nevertheless, in this exploratory study, we identified three classes of CRF that had different associations with sleep quality, anxiety, anhedonia, and lifestyle factors.…”
Section: Discussionmentioning
confidence: 78%
“…As such, the results of this exploratory study should be cautiously interpreted. Although the MFI purports to assess five dimensions of fatigue, these dimensions have not been wholly replicated [49]. Nevertheless, in this exploratory study, we identified three classes of CRF that had different associations with sleep quality, anxiety, anhedonia, and lifestyle factors.…”
Section: Discussionmentioning
confidence: 78%
“…Fatigue is a complex interaction between a disease process and factors such as muscle fatigue, self-perceived feelings of fatigue, and the individual's environment [34,41]. To address these issues, fatigue assessment instruments must be easy for individuals to understand and complete, must be capable of measuring the impact of therapeutic interventions, and have robust psychometric properties (Table 2) [42]. The literature review and surveys described herein underscore the need for a validated scale to measure fatigue in patients with GD.…”
Section: Discussionmentioning
confidence: 99%
“…MS-related fatigue is mostfrequently defined as "a subjective lack of physical and/or mental energy that is perceived by the individual or caregiver to interfere with usual and desired activities" (Multiple Sclerosis Council for Clinical Practice Guidelines, 1998, p.2); however, multiple definitions exist (e.g., Comi, Leocani, Rossi, & Colombo, 2001;Mills & Young, 2008). Measuring fatigue is equally complex, and multiple self-report tools -of varying psychometric quality -are available to quantify subjective fatigue retrospectively in chronic illness (Whitehead, 2009).…”
Section: Ms-related Fatiguementioning
confidence: 99%